Ontological Security, Trauma and Violence, and the Protection of Women: Polygamy Among Minority Communities - Harel-Shalev, Ayelet; Kook, Rebecca (Frontiers in Psychology, 2021)
In this article we examine the special challenges posed by the practice of polygamy to minority women, focusing on the ways that the state and the women confront the related experiences of violence and trauma associated with this practice. Based on analysis of both policy and interviews with women, we demonstrate the tension between the different mechanisms adopted by the state as opposed to those adopted by the women themselves. We suggest that the concept of ontological security is valuable for a deeper understanding of the range of state motivations in cases related to minority women, violence and the right for protection. Our case study is the Bedouin community in Israel. We explore the relationship between individual and state-level conceptions of violence and trauma and the complex relationship between these two. We examine state discourses of ontological security through a gendered lens, as frameworks of belonging and mechanisms of exclusion.